Prevalence of thyroid nodules and canceration risk assessment in TIRADS, and their relationships to obesity and dysglycemia - Wang, Weikang; Xiao, Ling; He, Mei; Feng, Ruimei; Huang, Xiaoyin; Su, Qingling; Xue, Xiujian; Hu, Zhijian; Zhang, Qian; Du, Shanshan; Lin, Hong; Ye, Weimin (Frontiers in Oncology, 2025)
ObjectiveTo describe the prevalence of thyroid nodules (TNs), their ultrasonographic characteristics, and the cancer risk assessment using the Thyroid Imaging Reporting and Data System (TIRADS) in a natural population, while also exploring their association with multiple metabolic disorders. This study aims to provide insight into the disease burden of TNs in the coastal area of Southeast China.DesignA cross-sectional study.Setting and participantsA total of 6221 participants from the baseline survey of the Fuqing Cohort Study, an ongoing population-based study in a coastal city of Southeast China, were included.Primary and secondary outcome measuresTNs and its detailed ultrasonographic characteristics, risk grading in TIRADS, and metabolic factors.ResultsThe age- and sex-standardized prevalence of TNs was found to be 67.2%, with a higher prevalence observed in females and an increase with age. Additionally, multiple, solid, and < 10 mm TNs were common. Approximately 39.2% of participants were diagnosed with grade 3, while 2.3% were classified as grade ≥ 4a according to TIRADS. Metabolic syndrome was associated with TNs, but this association was significant only in females. The relationship between metabolic disorders and the characteristics and grade of TNs in TIRADS varied by sex.ConclusionThe prevalence of TNs in the coastal area of Southeast China is notable, with 2.3% of the population classified as grade ≥ 4a in TIRADS, indicating a high risk of cancer and necessitating further assessment for thyroid cancer. The association between TNs and metabolic disorders varies by sex and requires further confirmation.